Primary cutaneous amyloidosis: A clinico-pathological study with emphasis on polarized microscopy - B Vijaya; Bibhas Saha Dalal; Sunila; G V Manjunath (Wolters Kluwer Medknow Publications, 2012)
Background: Primary localized cutaneous amyloidosis (PCA) is a relatively rare condition characterized by amyloid deposition in dermis without systemic involvement. Although, histopathological examination of the lesion reveals amorphous eosinophilic deposits in papillary dermis examination of congo red stained slides under polarized light will give definitive diagnosis Aims: To study the clinicopathological features of cutaneous amyloidosis emphasizing the utility of polarized light in diagnosis. Materials and Methods : A clinicopathological study of primary cutaneous amyloidosis over a period of 8 years was undertaken. All the cases, clinically diagnosed and histopathologically proven as cutaneous amyloidosis were stained with congo red and studied under polarized light. Results and Conclusions: Of the 45 cases of clinically suspected amyloidosis, 32 cases were proven histopathologically as primary cutaneous amyloidosis and confirmed by congo red stain under polarized light which showed apple green birefringence. Among the two types of PCA, lichen amyloidosis was the most common variant accounting to 65.63% with pure cases of macular amyloidosis accounting for only 15.63%. Biphasic amyloidosis was seen in 18.75%. Knee was the commonest site of involvement with pruritis being the most common symptom. Histopathologically, the most common findings were hyperkeratosis, irregular acanthosis and expansion of dermal papillae by amyloid deposits showing apple green birefringence under polarized microscope with congo red staining. Although, H and E stain gives a clue for the diagnosis of amyloid nevertheless congo red staining under polarized light forms a very sensitive and definitive method for confirmation.